Vision-based structural vibration displacement measurement and modal identification - Tan, Dong (Curtin University, 2024)
Accurate measurement of structural vibrations is a critical task in the realm of civil engineering. The installation has hindered the wide usage of traditional sensors. In recent decades, computer vision-based techniques have been introduced to offer an alternative to traditional displacement measurements, especially with the popularisation of apparatus like cameras and Unmanned Aerial Vehicle. This thesis will propose a few vision-based techniques to deal with the problems in structural vibration measurement and modal analysis.